Variabilitas musiman terhadap hasil tangkapan Tuna Madidihang (Thunnus albacares): Seasonal variability of catch results of madidihang tuna (Thunnus albacares) - Kedswin Hehanussa; Stany R. Siahainenia; R. H. S. Tawari (Universitas Sam Ratulangi, 2024)
Fishermen in North Buru often depend on seasonal changes in tuna madidihang abundance to plan their fishing operations. However, a more comprehensive understanding of how this seasonal variability affects catches and its implications for fisheries management is still an important research subject. The research was conducted in Wailihang Village, Waplau District, North Buru Regency, between October and December 2022. The observational method was used for this study, where available and precise time series data owned by the Indonesian Community and Fisheries Foundation (MDPI) was collected. The collected data is the number of catch productions (kg) and the total length of fish (cm) from each haul. Yellowfin tuna production tends to fluctuate, with the highest catch (CPUE) occurring in September (63.8%) and the lowest in June (34.2%). The west season and east seasons have a total catch of 556 fish (45.42%), with 382 fish (31.21%) caught during the east season and 174 fish (14.22%) caught during the west season. The distribution of fish length varies in the east season compared to the west season. The west season catches more fish, but they are generally small-sized, while during the east season, large fish dominate, with the highest presentation (38.67%).